From geriatric assessment to inflammation. A pilot, observational, study about frailty components in older patients with persistent atrial fibrillation - Stefano Fumagalli; Giulia Ricciardi; Claudia Di Serio; Elisa Berni; Giancarlo La Marca; Giuseppe Pieraccini; Riccardo Romoli; Emanuele Santamaria; Giulia Spanalatte; Camilla Cagnoni; Arianna Tariello; Giada Alla Viligiardi; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: Atrial fibrillation (AF) is the most common arrhythmia diagnosed at an older age. AF is associated with frailty, a condition possibly justifying the higher rate of complications and mortality in aged individuals. This study was aimed at describing the characteristics correlated to frailty in older AF subjects. Methods: After having excluded a < 3 months major surgery procedure, cancer or other conditions associated with activation of inflammation, and a life expectancy < 12 months, we consecutively enrolled patients ≥ 65 years with persistent AF. They underwent a Comprehensive Geriatric Assessment evaluation. In particular, Mini-Mental State Examination, 15-item Geriatric Depression Scale and Short-Physical Performance Battery (SPPB) described, respectively, cognitive profile, depressive symptoms and physical performance. A venous blood sample was collected to measure interleukin-6 (IL-6; marker of low-grade inflammation) and acylcarnitines, expression of mitochondrial dysfunction and abnormal energy production. Results: Overall, 49 patients (mean age: 76 ± 6 years; women 30.6 %) were studied. Cluster analysis described two different patterns; the second (N = 18, 36.7 %), when compared to the first one (N = 31, 63.3 %), was characterized by a worse phenotype, identified by the simultaneous presence of lower body mass index, higher CHA2DS2-VASc score (index of clinical complexity), worse SPPB functional performance, and high IL-6 levels. Second cluster patients had a higher concentration of 13 of the 35 acylcarnitines evaluated and increased 5-year mortality. All these features can outline a frail condition. Conclusions: Body size, clinical complexity, physical performance and low-grade inflammation seem to rapidly and adequately describe frailty.